Bexotegrast in people with idiopathic pulmonary fibrosis (IPF): a plain language summary of publication of the INTEGRIS-IPF study - Lisa Lancaster; Vincent Cottin; Murali Ramaswamy; Wim A. Wuyts; R. Gisli Jenkins; Mary Beth Scholand; Michael Kreuter; Claudia Valenzuela; Christopher J. Ryerson; Jonathan Goldin; Grace Hyun J. Kim; Marzena Jurek; et al. (Therapeutic Advances in Respiratory Disease)
What is this summary about? This plain language summary shares results from a clinical study called INTEGRIS-IPF that was published in the American Journal of Respiratory and Critical Care Medicine in 2024. This study looked at a medicine called bexotegrast (beck-so-teh-grast) as a possible treatment for idiopathic pulmonary fibrosis (i-dee-uh-pa-thick pul-muh-ner-ee fie-bro-sis; IPF). Bexotegrast is an investigational medicine, which means that it is being studied and has not yet been approved by the US Food and Drug Administration (FDA), for people with IPF to take as a treatment. IPF is a chronic, progressive lung disease that makes it hard to breathe and gets worse over time. There is no cure for IPF, treatment includes symptom management and consideration for the use of nintedanib or pirfenidone , which may decrease the pace of disease progression. The study compared bexotegrast to a placebo (a treatment that looks identical to the medicine but has no medicinal effect) to look at how well it works and how safe it is in treating people with IPF. Most people in the study also took one of two medicines that are already approved by the FDA for IPF, pirfenidone or nintedanib .